Kualitas Kefir Susu Sapi dengan Tambahan Madu Hutan Selama Penyimpanan Suhu Rendah - Nurina Hadiati Rachmani; Epi Taufik; Astari Apriantini; Yuni Cahya Endrawati (Jurnal Ilmu Pertanian Indonesia, 2023)
Kefir is a highly acidic dairy product with various health benefits. The addition of forest honey plays a role in improving the quality and taste of kefir. This study aimed to evaluate the effect of honey addition and storage time on the physicochemical and organoleptic properties of cow's milk kefir during refrigerator storage. The study was conducted with a 3´3 factorial randomized block design with three replications. The first factor was the added honey (0%, 5%, 10%, and 15%), and the second was the storage time (0, 7, and 14 days). Analysis of variance and Duncan's test were used to analyze the data. The results showed that the added honey significantly affected water activity (P <0.05). In addition, the high concentration of added honey increased the panelists’ preference for kefir acceptance. This study confirmed that the addition of honey and storage time significantly affected the characteristics of the cow's milk kefir. The best treatment was a 15% addition of honey with a storage time of 0 day. Keywords: honey, kefir, milk, physicochemical, storage time